Sebuah Reviu terhadap Kajian Partikel Pragmatik dalam Beberapa Bahasa Daerah di Indonesia - Agwin Degaf; NFN Irham; Zainur Rofiq (Ranah: Jurnal Kajian Bahasa, 2020)
This paper aims to demonstrate studies of pragmatic particles in Indonesian vernacular languages. Given the fact that Indonesia ranked second most populated language in the world after New Guinea, we would expect a huge number of studies discussing Indonesian local languages. Review to studies of pragmatic particles in Indonesian language is therefore considered salient to carry out to shed light on how different authors examine different particles, what kind of method they employ to describe meaning and functions, and what potential implication this study could contribute in this field. Besides, it also enriches the cross-linguistic study of pragmatic particles in general. Following Macaro et al’s. (2017) guideline of systematic review, this study employed linear process of procedure by deciding keywords, screening title, reviewing abstract, examining full text, and drawing conclusion. The corpus of pragmatic particles employed in reviewed studies ranges from colloquial, spoken, dialogue, and monologue data. Some approaches were used to reveal the pragmatic meanings, such as conversation analysis approach, pragmatics, morpho-syntactic, and even phonological approach. This discussion in the present paper may be fruitful for researchers who are working on pragmatic particles or vernacular languages and suggests that more studies in local languages should be outstripped to sustain national linguistic identity in the global arena.   AbstrakThis paper aims to demonstrate studies of pragmatic particles in Indonesian vernacular languages. Given the fact that Indonesia ranked second most populated language in the world after New Guinea, we would expect a huge number of studies discussing Indonesian local languages. Review to studies of pragmatic particles in Indonesian language is therefore considered salient to carry out to shed light on how different authors examine different particles, what kind of method they employ to describe meaning and functions, and what potential implication this study could contribute in this field. Besides, it also enriches the cross-linguistic study of pragmatic particles in general. Following Macaro et al’s. (2017) guideline of systematic review, this study employed linear process of procedure by deciding keywords, screening title, reviewing abstract, examining full text, and drawing conclusion. The corpus of pragmatic particles employed in reviewed studies ranges from colloquial, spoken, dialogue, and monologue data. Some approaches were used to reveal the pragmatic meanings, such as conversation analysis approach, pragmatics, morpho-syntactic, and even phonological approach. This discussion in the present paper may be fruitful for researchers who are working on pragmatic particles or vernacular languages and suggests that more studies in local languages should be outstripped to sustain national linguistic identity in the global arena.